BCL-X(L) overexpression promotes tumor progression-associated properties - Trisciuoglio, Daniela (Cell Death Dis, 2017)
By using human melanoma and glioblastoma cell lines and their derivative BCL-X(L) overexpressing clones, we investigated the role of BCL-X(L) in aggressive features of these two tumor histotypes. We found that in both models, BCL-X(L) overexpression increased in vitro cell migration and invasion and facilitated tumor cells to form de novo vasculogenic structures. Furthermore, BCL-X(L) overexpressing cells exhibited higher tumors sphere formation capacity and expressed higher levels of some stem cell markers, supporting the concept that BCL-X(L) plays essential roles in the maintenance of cancer stem cell phenotype. BCL-X(L) expression reduction by siRNA, the exposure to a BCL-X(L)-specific inhibitor and the use of a panel of human melanoma cell lines corroborated the evidence that BCL-X(L) regulates tumor progression-associated properties. Finally, the vascular markers and the vasculogenic mimicry were up-regulated in the BCL-X(L) overexpressing xenografts derived from both tumor histotypes. In conclusion, our work brings further support to the understanding of the malignant actions of BCL-X(L) and, in particular, to the concept that BCL-X(L) promotes stemness and contributes to the aggressiveness of both melanoma and glioblastoma.